Safety Evaluation of the Ethyl Acetate Extract on Irradiated Tea Parasite: Acute Toxicity Study on Mice - Hendig Winarno (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2011)
Many studies of the pharmacological efficacy of tea parasite and the use of ionizing radiation for decontamination of microbes and extending shelf life have been reported, but there is no information on its safety, such as the acute toxicity. In this study, the acute toxicity of two ethyl acetate extracts from unirradiated and irradiated (irradiation dose of 10 kGy) tea parasites Scurrula atropurpurea on Swiss Webster mice have been examined. The observation was done after the treatment of a single oral dose of ethyl acetate extract in various dose groups, i.e.: control (0 g/kg of mice body weight), D1 (0.625 g/kg), D2 (1.25 g/kg), D3 (2.5 g/kg) D4 (5 g/kg), D5 (10 g/kg) by observing the effect on behavioral response (pharmacological profile), the body weight gains and mortality until the day 14 th . At the last day, the observation of vital organs has also been done. The result showed thatno acute toxicity was found in mice treated with a single oral dose of ethyl acetate extract from unirradiated tea parasite and irradiated tea parasite at the dose of 10 kGy. At the dose up to 10 g/kg (equivalent to 77.6 g of extract which administered to human), the normal body weight gains were observed in mice of all dose groups, no mice deaths in any of the dose groups, and no significant change (p > 0.05) in organ weights relative to the body weight i.e.: liver, spleen, kidneys, lung, heart, testes and seminal vesicle (for male), and ovaries and uterus (for female). The approximate lethal doses for male and female mice were determined to be higher than 10 g/kg of mice body weight. It is suggested that the treatment of ethyl acetate extract from unirradiated and irradiated tea parasites until dose up to 10 g/kg of mice body weight was stillsafe.